The relationship between family factors and academic achievement of junior high school students in rural China: mediation effect of parental involvement - Gu, Xiaoxia; Hassan, Norlizah Che; Sulaiman, Tajularipin (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study aims to understand how socioeconomic status and the family environment impact students’ academic achievement through the mediation of parental involvement in rural China. To achieve this, a cross-sectional design was adopted, and a total of 525 parents of rural junior high school students from S province in southwest China were surveyed. The proposed conceptual framework was tested by structural equation modeling. The results claimed that both socioeconomic status and the family environment are important factors affecting the academic achievement of rural students, and the role of the family environment is more pronounced. Furthermore, parental involvement has a significant mediating effect between socioeconomic status and academic achievement, especially between the family environment and academic achievement. The findings highlighted the importance of the family environment and parental involvement to compensate for the negative impact of disadvantaged family socioeconomic status on academic achievement. © 2024 by the authors.